When surgery leaves more than just scars: The curious case of gossypiboma— A case report and literature review - Syed Muhammad Ali, MBBS; Affan Faisal, MBBS; Talha Ashraf Zia, MBBS; Fatima Shahid, MBBS; Muhammad Nabeel Saddique, MBBS; Anurag Jha, MBBS; Atif Hussain Sarwar, MD; Javed Iqbal, RN, PhD (Radiology Case Reports)
Gossypiboma is a unique postoperative complication characterized by the presence of a surgical sponge after surgery. This condition is seldom encountered. Owing to its serious medicolegal implications it remains underreported leading to a blurred clinical spectrum. This fact is also depicted in our case which presents an array of nonspecific symptoms painting a picture of possible malignancy. The case highlights the need for strict adherence to surgical protocols to avoid such instances of clinical negligence. Furthermore, our report provides the medical community with apt data to promptly diagnose such cases. A 40-year-old Asian hypertensive and diabetic female with a history of total hysterectomy presented with a 7-month history of progressive abdominal swelling, vomiting, and weight loss. The initial clinical presentation pointed to possible malignancies but subsequently revealed a 16 × 4 × 6 cm gossypiboma near the ileocecal junction. Following the removal and resection of 2.5 feet of the ileum, the patient underwent a right hemicolectomy, ileostomy, and colostomy. The postoperative recovery was uneventful, and the patient was discharged in stable condition. This case reiterates the importance of adhering to established surgical protocols and how minor negligence can have devastating and horrid effects. This case highlights the need for the fusion of medicine with technology< which prompts the use of innovations such as RFID-tagged sponges and electronic counting to minimize human error. Increased awareness and reporting of gossypibomas will aid in their timely diagnosis and management, ultimately reducing patient morbidity and associated legal challenges.